1998
DOI: 10.1292/jvms.60.1149
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between Chondroma and Squamous Cell Carcinoma: Evaluation of Subtraction Image of MRI.

Abstract: ABSTRACT. The image processing procedure has become widely applied as a visual aid in imaging diagnosis. The subtraction image of MRI obtained by digitally subtracting an unenhanced image from a contrast-enhanced image, depicted a discrete distribution of the contrast agent. Subtraction images in the clinical cases were compared. The subtraction image in a case of chondroma demonstrated a relatively uniform distribution of a contrast agent, with a well delineated neoplastic lesion. The subtraction image in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…One study concluded that subtraction images increase the conspicuity of normal canine meninges ( 19 ). One case report describes subtraction images being used to differentiate chondroma and squamous cell carcinoma in two beagle dogs ( 20 ). Another study reports improved detection of meningeal, articular and muscular contrast enhancement in the spine of dogs afflicted with steroid responsive meningitis arteritis ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…One study concluded that subtraction images increase the conspicuity of normal canine meninges ( 19 ). One case report describes subtraction images being used to differentiate chondroma and squamous cell carcinoma in two beagle dogs ( 20 ). Another study reports improved detection of meningeal, articular and muscular contrast enhancement in the spine of dogs afflicted with steroid responsive meningitis arteritis ( 21 ).…”
Section: Introductionmentioning
confidence: 99%